Gadget dalam Pembelajaran: Analisis Komparatif Progresivisme dan Rekonstruksionisme serta Relevansinya dengan Pendidikan Islam - Hurul Ain; Zuhrotus Saniyyah; M. Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of digital technology has made gadgets an inseparable part of education, bringing both positive impacts and challenges for students' character formation. This study aims to analyze the similarities and differences between progressivism and reconstructionism perspectives on gadget utilization, and integrate them with Islamic education philosophy values. A qualitative research method with library research approach was used through descriptive-comparative analysis of relevant literature sources. The results show that progressivism views gadgets as tools for individual development through active learning, while reconstructionism emphasizes gadget's transformative function for social change. Integration of these two perspectives within Islamic education philosophy framework produces a conceptual framework that balances technological advancement with value-based character building. This study concludes the importance of philosophical approach in viewing gadget utilization to ensure not only pedagogical effectiveness but also moral and spiritual meaningfulness.